EVALUATION OF VARIANTS OF SURGICAL INTERVENTIONS FOR ACUTE CALCULOSIS CHOLECYSTITIS IN PATIENTS OF ELDERLY AND SENIOR AGE (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
The nature of the complex surgical treatment of acute calculous cholecystitis in elderly and senile patients, under the conditions of gradation age analysis, made it possible to identify a number of theoretical patterns, such as the dependence of the degree of complexity of surgical intervention on the severity of acute calculous cholecystitis, which is not reliable. In most cases, a similar peak value in this rank appears among patients with moderate severity of acute calculous cholecystitis. The ranking of patients in this subgroup between mild and severe severity of the disease does not allow achieving compliance with the planned type of surgical intervention. In our research, this is confirmed by a high level of conversion cases and an increase in the share of the degree of complexity.